Optimalisasi Progam Kalimasada Oleh Mahasiswa MSIB6 Dalam Pendistribusian Kartu Identitas Anak Di Kelurahan Medokan Ayu - Anisatul Septian Ika Candra; Kendry Widiyanto (Journal of Research and Development on Public Policy, 2024)
The dense population in Medokan Ayu Village is enough to make the need for population identity services increase every day. Detected not only for the population identity of those aged 17 years and over, such as KTP, but also for those aged less than 17 years, namely the Child Identity Card (KIA), which is no less important as a guide in protecting children. With this, ownership goals (KIA), especially in Medokan Ayu Village, are included in the category of not yet optimal and uneven. As a result of parents' lack of insight and understanding regarding the manufacture of (KIA), it can be ascertained that this is one of the causes of unequal distribution of ownership (KIA) to the maximum. The solution is to use a method with several stages as follows 1.) Identifying ownership (KIA) 2.) Assistance with management services (KIA) 3.) Distribution of printed Child Identity Cards (KIA). With this, it is hoped that the assistance efforts that we are organizing can help in increasing ownership (KIA), especially in Medokan Ayu Village. Because as more and more people have (KIA), children under 17 years of age can have their rights fulfilled. It can be concluded that the awareness of the Medokan Ayu Village community regarding ownership of population administration documents is quite orderly, however, in terms of the implementation of applications for population administration documents, especially Child Identity Cards (KIA), it can still be said to be lacking.